2001
DOI: 10.4049/jimmunol.166.11.6728
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Controls Intracellular Mycobacterial Growth by Both Inducible Nitric Oxide Synthase-Dependent and Inducible Nitric Oxide Synthase-Independent Pathways

Abstract: The role of TNF-α in the control of mycobacterial growth in murine macrophages was studied in vitro. Infection of macrophages from TNF-α gene disrupted (TNF-knockout (KO)) mice with recombinant Mycobacterium bovis bacillus Calmette Guérin (BCG) expressing the vector only (BCG-vector) resulted in logarithmic growth of the intracellular bacilli. Infection with BCG-secreting murine TNF-α (BCG-TNF) led to bacillary killing. Killing of BCG-TNF was associated with rapid accumulation of inducible NO synthase (iNOS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 33 publications
5
79
0
1
Order By: Relevance
“…Most bacteria activate iNOS in macrophages after invasion (21) or by an LPS-mediated pathway (22). Herein, we demonstrate that soluble H. pylori-released proteins cause NO generation by macrophages.…”
Section: Discussionmentioning
confidence: 75%
“…Most bacteria activate iNOS in macrophages after invasion (21) or by an LPS-mediated pathway (22). Herein, we demonstrate that soluble H. pylori-released proteins cause NO generation by macrophages.…”
Section: Discussionmentioning
confidence: 75%
“…IFN-␥ is clearly indispensable for resistance to mycobacterial and other intracellular infections (17) and is often used as a single readout for Th1 responses. TNF-␣ is on its own an effector cytokine that can synergize with IFN-␥ to eliminate intracellular pathogens (18,19). It is interesting, therefore, that on a per cell basis the multifunctional cells were 2-4 times more efficient producers of the measured cytokines than the single-positive CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a was found in the lungs of mice experimentally infected with Chlamydia trachomatis and showed that exogenous TNF-a, induced by lipopolysaccharide provided protection from death caused by the pathogen. The presence of TNF-a whether of host or pathogen origin was required [32]. …”
Section: Discussionmentioning
confidence: 99%